Tiedonarkeologisia pohdintoja Viipurin vuoden 1918 haudatuista muistoista - Fingerroos, Outi (Viipurin Suomalaisen Kirjallisuusseuran toimitteita, 2021)
Knowledge-archaeological reflections on the buried memories of Vyborg in 1918 The subject of the article is the ‘memory war’ over the memory of the Civil War of 1918 in Vyborg, and the displaced Karelians’ experience in the time of diaspora. Until the wars of 1939–1945 the culture of remembrance of the Civil War was divided in Vyborg and in Finland and many truths of the war were maintained in the Red’s and White’s own groups. The article details how the dichotomous history culture of Civil War memories has slowly transformed into a diversified and critical analysis over the past one hundred years. The qualita- tive material used in the article consists of memory data written by displaced Karelians held in Finnish archives. The article is a knowledge-archaeological analysis of memories, memorial culture, and sedimentary layers from different times in history.